FUNGSI PENGAWASAN INSPEKTORAT TERHADAP PERANGKAT DAERAH (PD) PEMERINTAH KOTA MANADO - Maria Grace Damopolii; Leonardus R. Rengkung R. Rengkung; Charles R. Ngangi (AGRI-SOSIOEKONOMI, 2017)
The purpose of this study is to analyze the function of supervision of the Manado City Inspectorate Office to the regional apparatus. The research method used is descriptive qualitative. This research is located in Manado City that is to Inspection Office of Manado City. The data collected in the form of reports on the results of supervisory activities are audit report, evaluation report, monitoring report and report result of review for 3 (three) years from 2013 until 2015 in the authorities and agencies in Manado City. In this study was used comparative data analysis. There are three main findings of this research are: firstly, from the analisis result of supervision function in the form of audit, evaluation, monitoring and review that have conducted by Inspectorate of Manado City toward Manado City Local Government Offices administration, there is a significant decrease of findings from all examination object or auditee. Secondly, from the decreasing number of findings indicates that the supervisory function performed by the Manado City Inspectorate on the Manado City Local Government implementation is done with good and optimal performance. Third, the influence of the Inspectorate's supervisory function on the performance of the regional apparatus of Manado City Government indicates that the Manado City Inspectorate has succeeded in performing its supervisory function as a quality assurance or guarantor of quality toward the performance of official of Local Governments in Manado City.